THE USE OF PERSONAL VOCABULARY NOTE (PVN) TO TEACH VOCABULARY - Tiabarte, Aulyahaq; Sutapa, Yohanes Gatot; Rosnija, Eni (Journal of English Education Program, 2020)
The objective of this study is to discover the effect of Personal Vocabulary Note (PVN) on the students vocabulary achievement. This form of research is a pre-experimental study. The research population on this research was the eighth-grade students that consisted of 43 students of SMP Negeri 1 Mempawah Timur. By using cluster random sampling, the sample was VIII B class, consisted of 21 students. The data on this study was gathered through a written test in form of multiple choice. The data showed that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected, means that Personal Vocabulary Note (PVN) affect significantly in teaching vocabulary for the eighth-grade students in SMP Negeri 1 Mempawah Timur. The result of t-test was 12.61. It was higher than t-critical(12.61 > 2.086). Finding also showed that the score of the effect size of the treatment was 2.73 and categorized as strong effect. It can be concluded that Personal Vocabulary Note (PVN) give a strong effect on vocabulary achievement of the eighth-grade students of SMP Negeri 1 Mempawah Timur in Academic Year 2019/2020.